Effects of a 24-week yoga intervention on choriocapillaris density in Parkinson’s disease - Lei Wan; Andrew Hoover; Giovana Rosa Gameiro; Amanda Virgets; Kylie J. Martinez; Joseph Signorile; Hong Jiang; Jianhua Wang (Clinical Parkinsonism & Related Disorders, 2025)
Introduction: Parkinson’s disease (PD) involves systemic microvascular dysfunction, with choriocapillaris density (CCD) potentially reflecting it. This study examined whether a 24-week yoga intervention alters CCD in PD and whether responses differ by disease duration, severity, or intervention style. Methods: Fifteen PD patients completed a supervised 24-week yoga program involving two Hatha-based styles. CCD was measured using 3 × 3 mm macular optical coherence tomography angiography (OCTA) centered on 2.5-mm foveal region. Clinical assessments included disease duration, Hoehn and Yahr (H&Y) stage, and Montreal Cognitive Assessment (MoCA), conducted at baseline and after intervention. Correlation, stratified, and subgroup analyses were performed. Results: No significant change in CCD was observed at the group level (62.9 % ± 3.9 % vs. 62.9 % ± 3.2 %; P > 0.05). Baseline CCD was inversely correlated with disease duration and H&Y stage (ρ = −0.71, P = 0.003). Patients with shorter disease duration (<5 years) or early-stage PD (H&Y stage 1) showed significant CCD reductions (ΔCCD = −4.7 %, P = 0.003; ΔCCD = −4.3 %, P = 0.002), whereas those with longer duration or advanced stage (H&Y 2–3) exhibited mild increases (ΔCCD = +2.3 %, ΔCCD = +2.8 %). Baseline CCD was inversely correlated with ΔCCD (ρ = −0.77, P < 0.001). CCD did not differ between the YogaCue and Hatha Yoga groups at baseline, follow-up, or in ΔCCD (P > 0.05). Conclusions: These findings provide preliminary evidence that CCD responses to yoga vary with disease stage but not intervention style, suggesting a potential role for CCD as a vascular marker to inform individualized rehabilitation in PD.